To know all mysteries : the mystagogue figure in classical antiquity and in Saint Paul's letters to the Corinthians /: the mystagogue figure in classical antiquity and in Saint Paul's letters to the Corinthians. (2022) - Ballard, C. Andrew, 1983-
No abstract available